Radio Direction Finding in Air Traffic Services - Novak, Andrej (Promet - Traffic&Transportation)
The paper analyses the Radio Direction Finding principlefor navigation and swveillance system. Radio Direction Findinginvolves locating the bearing of a transmitter called a radiobeacon. A radio beacon’s signal is received aboard a vehicle bya device called radio direction finder (RDF). The navigatorturns the antenna of the radio direction finder to find the directionof the radio beacon. The RDF shows when the antenna ispointing towards the beacon. Radio direction finding is one ofthe oldest electronic navigation systems for aircraft and ships. Itis generally used as a piloting aid along coastal waters. Therange of a radio direction finding signal depends on the type ofradio beacon.